Contributions to the history of documentation and information science : An overview of the development of documentation and information science in the 20th century in German-speaking countries (Libellarium: journal for research in the field of information and related sciences, 2023)
Purpose. The aim of the article is to provide an overview and critical observations on the development of documentation and information science in the German speaking countries. Since until now, except in the German language, no complete review has been written onhow documentation studies developed and what their relationship to librarianship was, and how and when the new paradigm shift to information science took place. Consequently, Croatian professionals in the field have been denied such knowledge.Approach/methodology. The article is based on a critical reading and interpretation of published secondary sources, especially articles and reports from the journals Nachrichten für Dokumentation (since 1990: Nachrichten für Informationswissenschaft), several other German journals and books, and all seven editions of the well-known manual Grundlagen für Dokumentation (later: Grundlagen für Informationswissenschaft).Results. The development path of German, Austrian and Swiss documentation and information science is presented as an overview. The problems and doubts faced by expertsfrom these areas as well as the uncertainty surrounding the definition of a new field are pointed out. The article is also characterized by the author’s interpretation of the insufficient argumentation of the reasons that led to the abandonment of the originally German documentation paradigm in support of taking over the paradigms advocated by experts from the Anglo-American environment.Research limitations. This paper is conceived as part of a series on the development of documentation and information science in several influential environments (American-British, Francophone, German and Russian/Soviet Union) and the influence of models and trends from those environments on the development of documentation and information science in the region of the former Yugoslavia with an emphasis on Croatia. Therefore, it is to be expected that until the publication of other review papers, the details problematized in this article may remain insufficiently clear.Social significance. In the Republic of Croatia, information sciences were endorsed as an academic and scientific discipline in 1983, so this anniversary stimulated research curiosity about determining the oldest sources of knowledge about the development trends in the second half of the 20th century. It is expected that this article could contribute to the understanding of the circumstances of the growth of information sciences as a young scientific field.Originality/value. The research was conducted on original materials written in German, and was enriched with comments based on the author’s knowledge and experience, who has followed this field since its official endorsement into the Croatian academic and scientific family until today.
Keywords: Austria; documentation; information science; information sciences; Germany; Switzerland